Analisis Pengendalian Intern Persediaan Obat-Obatan pada UPT Puskesmas Desa Binjai - Irene Nauli Limbong; Mangasa Sinurat; Herti Diana Hutapea (VISA: Journal of Vision and Ideas, 2024)
The purpose of this research is to find out how to implement the elements of internal control of medicine supplies at the Binjai Village Community Health Center. The research method used was a qualitative method. The data used are primary data and secondary data, with data collection techniques namely observation, data and conclusions. The results of the conclusions show that First, the implementation of internal control of drug supplies at the Binjai Village Health Center is sufficient starting from planning procedures, requests, receipts, storage, control, recording, reporting and archiving as well as monitoring and evaluating drug management are in accordance with applicable Standard Operating Procedures. Second, the Binjai Village Health Center has implemented most of the internal control activities on medicine supplies well, so it can be said that internal control has been carried out effectively. Third, in terms of elements of drug supply control, it is good.